Antropomorphic statuettes from Cucuteni-Tripolye - Lazarovici, Cornelia-Magda (Documenta Praehistorica, 2005)
Our article present anthropomorphic statuettes from the area of the Cucuteni-Tripolye culture with signs and symbols related to sacred messages used during cultic ceremonies. We also present older and newer opinions on this subject. Signs and symbols help us to decipher some aspects of the religious life of that time.
Keywords: Romania; Romunija; arheološke najdbe; eneolitik; kipi; obredi; simboli; symbol